Temperature dependent photoluminescence study of ZnO thin fim. - Guo, Min. (2009)
In this paper, there are four chapters to be covered: photoluminescence spectroscopy, photoluminescence theory, properties and applications of ZnO, and lastly temperature dependent PL study of ZnO thin film. First of all, photoluminescence spectroscopy is introduced, from its components, setup, application and operations. Main components of the spectroscopy are explained in details, including the excitation source, optics, detector and signal acquisition. Secondly, a complete review of photoluminescence theory is written together with measurement technique and a detailed experimental procedure. Next, a detailed review of structural and optical properties of bulk ZnO is provided, together with a review of ZnO-based LED. This explains the motivation behind this whole project. After that, the experimental results are presented and proper interpretations are provided.